Increased Oxidative Stress Tolerance by Cambialistic Superoxide Dismutase Overexpression in Mesorhizobium japonicum MAFF303099 - Gonzalez, Pablo; Lozano, M.; Lascano, Hernan Ramiro; Lagares, Antonio; Melchiorre, Mariana (Ediciones INTA, 2024)
Oxidative stress is a common denominator underlying many environmental insults. As a global response, the increment of intracellular reactive oxygen species leads to the activation of the antioxidant system to maintain cellular homeostasis. The Mesorhizobium japonicum MAFF303099 mlr7636 SOD gene was constitutively overexpressed to test if the enhanced superoxide dismutase (SOD) activity contributes to oxidative stress tolerance in free-living cells. Salt stress, decreases in the osmotic potential, and superoxide generation by killing assays were assayed in cultures of M. japonicum with a constitutive SOD overexpression under the nptII promoter of pFAJ1708 plasmid to evaluate bacterial survival. The results showed that the strain carrying an additional mlr7636 copy had five-fold increased SOD activity in the periplasmic space using Fe as a cofactor, and that its higher tolerance to oxidative stress was related to high SOD activity per se, which contributes to fast superoxide dismutation associated with hydrogen peroxide reduction by increases in Catalase activity. To our knowledge, this is the first report of homologous superoxide dismutase overexpression in M. japonicum, which contributes to the description of its role in the tolerance to oxidative stress under free-living conditions.